The Glucocorticoid Receptor Polymorphism Landscape in Patients With Diamond Blackfan Anemia Reveals an Association Between Two Clinically Relevant Single Nucleotide Polymorphisms and Time to Diagnosis - Lonetti, Annalisa; Indio, Valentina; Dianzani, Irma; Ramenghi, Ugo; Da Costa, Lydie; Pospíšilová, Dagmar; Migliaccio, Anna Rita (Frontiers in Physiology, 2021)
NR3C1 encoding the glucocorticoid receptor, is polymorphic presenting numerous single nucleotide polymorphisms (SNPs) some of which are emerging as leading cause in the variability of manifestation and/or response to glucocorticoids in human diseases. Since 60% of patients with Diamond Blackfan Anemia (DBA), an inherited pure red cell aplasia induced by mutations in ribosomal protein genes, became transfusion independent upon treatment with glucocorticoids, we investigated whether clinically relevant NR3C1 SNPs are associated with disease manifestation in DBA. The eight NR3C1 SNPs rs10482605, rs10482616, rs7701443, rs6189/rs6190, rs860457, rs6198, rs6196 and rs33388/rs33389 were investigated in 91 European DBA patients. Results were compared with those observed in healthy volunteers (n=37) or present in public databases of Italian and European populations. Although, cases versus control analyses suggests that the frequency of some of the minor alleles is significantly altered in DBA with respect to healthy controls, or to the Italian or European registries, lack of consistency among associations across different sets suggests that overall the frequency of these SNPs in DBA is not different from that of the general population. Demographic data (47 females and 31 males) and driver mutations (44 S and 29 L genes and 8 no-known mutation) are known for 81 patients while glucocorticoid response is known for 81 (36 responsive, 45 non-responsive) and age of disease onsets for 79 (55 before and 24 after 4-months of age) patients. Neither gender nor leading mutations were associated with the minor alleles or with disease manifestation. Furthermore, none of the SNPs met the threshold in the response vs non-responsive groups. However, two SNPs (rs6196 and rs860457) were enriched in patients manifesting the disease before 4-months of age. Although the exact biomechanistical consequences of these SNPs are unknown, the fact that their configuration is consistent with that of regulatory regions, suggests that they regulate changes in glucocorticoid response during ontogeny. This hypothesis was supported by phosphoproteomic profiling of erythroid cells expanded ex-vivo indicating that glucocorticoids activate a ribosomal signature in cells from cord blood but not in those from adult blood. possibly providing a compensatory mechanism to the driving mutations observed in DBA before birth.